Octopamine modulates the innate immune response in Drosophila melanogaster - Uliczka, Karin; Papenmeier, Stephanie; Höschler, Beate; Wagner, Christina; Roeder, Thomas; Heine, Holger (Frontiers in Immunology, 2026)
BackgroundOctopamine, the functional equivalent of noradrenaline in invertebrates, is a key neuromodulator that also influences immune functions. However, the receptor‑specific roles of octopamine in regulating innate immunity in Drosophila melanogaster remain incompletely understood.MethodsUsing loss‑of‑function mutants for the two major octopamine receptors Octβ1R and Octβ2R, combined with systemic bacterial infection models, bacterial clearance assays, in vivo and in vitro phagocytosis assays, and quantification of antimicrobial peptide (AMP) gene expression, we dissected the contribution of each receptor to distinct immune effector modules.ResultsFlies deficient in Octβ1R or Octβ2R exhibited reduced survival and impaired bacterial clearance following systemic infection, which was associated with increased bacterial persistence. This phenotype correlated with reduced phagocytic activity of hemocytes in both in vivo and in vitro assays. In contrast, deficiency of Octβ1R or Octβ2R led to enhanced induction of a subset of essential AMP genes upon infection, indicating that octopamine signaling dampens specific humoral immune outputs.ConclusionOur data demonstrate that octopamine exerts a decisive influence on the performance of the Drosophila innate immune system by differentially modulating cellular (phagocytosis) and humoral (AMP expression) immune modules in a receptor‑specific manner. These findings establish octopaminergic signaling through Octβ1R and Octβ2R as an important node of neuro‑immune regulation in invertebrates.